Mesenchymal stem cell-derived exosomes protect trabecular meshwork from oxidative stress - Ying-chao Li (Nature Portfolio, 2021)
Abstract This study aims to investigate the beneficial effects of exosomes derived from bone marrow mesenchymal stem cells (BMSCs) on trabecular meshwork cells under oxidative stress and predict candidate genes associated with this process. Trabecular meshwork cells were pretreated with BMSC-derived exosomes for 24 h, and exposed to 0.1 mM H2O2 for 6 h. Survival rate of trabecular meshwork cells was measured with CCK-8 assay. Production of intracellular reactive oxygen species (iROS) was measured using a flow cytometer. RT-PCR and ELISA were used to detect mRNA and protein levels of inflammatory cytokines and matrix metalloproteinases (MMPs). Sequencing of RNA and miRNA for trabecular meshwork cells from Exo and control groups was performed on BGISEQ500 platform. Phenotypically, pretreatment of BMSC-derived exosomes improves survival rate of trabecular meshwork cells exposed to H2O2, reduces production of iROS, and inhibits expression of inflammatory cytokines, whereas increases expression of MMPs. There were 23 miRNAs, 307 lncRNAs, and 367 mRNAs differentially expressed between Exo and control groups. Exosomes derived from BMSCs may protect trabecular meshwork cells from oxidative stress. Candidate genes responsible for beneficial effects, such as DIO2 and HMOX1, were predicted.